Quantitative super-resolution single molecule microscopy dataset of YFP-tagged growth factor receptors - Lukeš, Tomáš; Pospíšil, Jakub; Fliegel, Karel; Lasser, Theo; Hagen, Guy M (GigaScience, 2018)
BACKGROUND: Super-resolution single molecule localization microscopy (SMLM) is a method for achieving resolution beyond the classical limit in optical microscopes (approx. 200 nm laterally). Yellow fluorescent protein (YFP) has been used for super-resolution single molecule localization microscopy, but less frequently than other fluorescent probes. Working with YFP in SMLM is a challenge because a lower number of photons are emitted per molecule compared with organic dyes, which are more commonly used. Publically available experimental data can facilitate development of new data analysis algorithms. FINDINGS: Four complete, freely available single molecule super-resolution microscopy datasets on YFP-tagged growth factor receptors expressed in a human cell line are presented, including both raw and analyzed data. We report methods for sample preparation, for data acquisition, and for data analysis, as well as examples of the acquired images. We also analyzed the SMLM datasets using a different method: super-resolution optical fluctuation imaging (SOFI). The 2 modes of analysis offer complementary information about the sample. A fifth single molecule super-resolution microscopy dataset acquired with the dye Alexa 532 is included for comparison purposes. CONCLUSIONS: This dataset has potential for extensive reuse. Complete raw data from SMLM experiments have typically not been published. The YFP data exhibit low signal-to-noise ratios, making data analysis a challenge. These datasets will be useful to investigators developing their own algorithms for SMLM, SOFI, and related methods. The data will also be useful for researchers investigating growth factor receptors such as ErbB3.
Keywords: fluorescenční barviva; Bacterial Proteins; algoritmy; luminescentní proteiny; Luminescent Proteins; Humans; receptory růstových faktorů; Algorithms; bakteriální proteiny; Receptors, Growth Factor; zobrazení jednotlivé molekuly; Single Molecule Imaging; lidé; Fluorescent Dyes